The impact of family interventions on communication in the context of anxiety and depression in those aged 14–24 years: systematic review of randomised control trials - Alex Lloyd; Amy Broadbent; Edmund Brooks; Karen Bulsara; Kim Donoghue; Rouhma Saijaf; Katie N. Sampson; Abigail Thomson; Pasco Fearon; Peter J. Lawrence (BJPsych Open, 2023)
Background The ability to communicate is integral to all human relationships. Previous research has specifically highlighted communication within families as both a risk and protective factor for anxiety disorders and/or depression. Yet, there is limited understanding about whether communication is amenable to intervention in the context of adolescent psychopathology, and whether doing so improves outcomes.